Surgical evaluation and knowledge transfer: methods of clinical research in surgery - Diener, Markus K.; Simon, Thomas; Büchler, Markus W.; Seiler, Christoph (Langenbeck's archives of surgery, 2012)
Purpose This article aims to outline the framework of surgical evaluation and knowledge transfer. Therefore, special design issues affecting surgical clinical research will be discussed. Moreover, principles and challenges of knowledge transfer from research into practice will be addressed.
Published online: 22 March 2011
Gesehen am 06.02.2019